2001
DOI: 10.1016/s0035-9203(01)90257-3
|View full text |Cite
|
Sign up to set email alerts
|

Long-term efficacy of single-dose combinations of albendazole, ivermectin and diethylcarbamazine for the treatment of bancroftian filariasis

Abstract: In a 'blinded' trial (in Sri Lanka, 1996-98) of 47 male asymptomatic microfilaraemic subjects with Wuchereria bancrofti infection, the safety, tolerability and filaricidal efficacy of 3 single-dose combination regimens were compared: albendazole 400 mg with ivermectin 200 micrograms/kg, albendazole 400 mg with diethylcarbamazine citrate (DEC) 6 mg/kg or albendazole 600 mg with ivermectin 400 micrograms/kg. Treated subjects were followed-up for 24 months. This represents the first long-term study using combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
1
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 9 publications
3
42
1
4
Order By: Relevance
“…[9][10][11][12] Some adult worms may die as a result of treatment with diethylcarbamazine (DEC), which causes painful inflammatory granulomas, especially in the intrascrotal lymphatic vessels in men. [13][14][15] A few clinical studies have assessed adverse reactions following treatment with DEC and albendazole, 9,16 but the burden of adverse reactions in large community-based interventions using DEC and albendazole has not been adequately documented. Little is known about the costs of adverse reaction management.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] Some adult worms may die as a result of treatment with diethylcarbamazine (DEC), which causes painful inflammatory granulomas, especially in the intrascrotal lymphatic vessels in men. [13][14][15] A few clinical studies have assessed adverse reactions following treatment with DEC and albendazole, 9,16 but the burden of adverse reactions in large community-based interventions using DEC and albendazole has not been adequately documented. Little is known about the costs of adverse reaction management.…”
Section: Introductionmentioning
confidence: 99%
“…8 In addition, several clinical trials showed that a single dose of ALB can reduce W. bancrofti microfilaria (mf) densities by 50% or more, and this reduction is sustained for 1 year or more after treatment. Of course, the decline in mf counts after ALB alone was slower and less dramatic than after combination treatment with either IVM + ALB or DEC + ALB, 9,10 but a small study found that a second dose of ALB given 1 year after the first led to a further decrease in mf counts. 11 The aim of MDA in LF elimination programs is to reduce the mf reservoir in populations to levels that cannot support sustained transmission of W. bancrofti by mosquitoes.…”
Section: Introductionmentioning
confidence: 99%
“…It is caused by the nematode parasites Wuchereria bancrofti, Brugia malayi, and Brugia timori, affecting Ͼ1.3 billion people in 81 countries worldwide, and several millions more are at risk of infection. The mainstay of filarial disease control has been a limited number of drugs, such as diethylcarbamazine, albendazole, and ivermectin, which are principally microfilaricidal, thus necessitating the need for repeated administrations (1,2). Furthermore, signs of emerging drug resistance are becoming increasingly apparent, especially against albendazole and ivermectin (3-5).…”
mentioning
confidence: 99%